Co-creation of information leaflets to meet the support needs of people living with Complex Regional Pain Syndrome (CRPS) through innovative use of wiki technology - Rodham, Karen; Gavin, Jeff; Coulson, Neil S.; Watts, Leon (Taylor & Francis, 2015)
Objective: People living with Complex Regional Pain Syndrome (CRPS) experience frustration with the lack of knowledge and understanding of CRPS as a pain condition. We report on our attempt to address this issue.